Pengaruh Pelatihan Bahasa Inggris Terhadap Kemampuan Komuniaksi Siswa Siswi di SD N 4 Tuban - Mulyawan, I Wayan; Putra, I Komang Sumaryana; Maharani, Sang Ayu Isnu; Rahayuni, Ni Ketut Sri (Humanis; Vol 26 No 2 (2022)DO - 10.24843/JH.2022.v26.i02.p10, 2022)
English Language Training for Students at SD 4 Tuban is one of the studies with the aim of improving students' abilities and competencies. It is one of the public elementary schools located in Kuta District, Tuban Village, Badung Regency. As one of the outstanding public elementary schools, it always maintains its good name and achievements through the performance of the teachers and their students. English as one of the compulsory subjects in addition to Balinese and Indonesian, is something that must be mastered by students considering that Badung Regency is one of the regencies that is famous for its tourism. The results of the study show that the use of the direct method, with game techniques and practice in pairs really helps improve students' creativity in communicating using English. Through this activity the students get a good learning experience, increase their confidence, and also improve their speaking and listening skills.